Satisfying result after endpoint management laser in acute central serous chorioretinopathy: a case report - Paramita, Anak Agung Diyananda; Andayani, Ari; Sudjana, Ni Made Ari Suryathi; Rahayu, Ni Made Kartika (International Journal of Advances in Medicine, 2024)
Central serous chorioretinopathy (CSC) is a condition where there is a buildup of fluid under the retina, specifically at the macula, causing neurosensory retinal detachment. This condition affected by many factors, one of them was psychological stress and male gender. CSC is a self-limiting disease, but in acute, chronic, and recurrent CSC in functionally monocular patient also could be considered as giving treatment. We presented a case of a 44 years old functionally monocular patient treated successfully with Endpoint management (EpM) Laser. After EpM laser was done, the subretinal fluid absorbed resolved, no darker spot straight ahead, and central foveal thickness in right eye was decreasing on the 14th day post operative. Treatment of CSC with visual loss is successful and efficient with EpM laser. Without harming retinal pigment epithelium, it accelerates sub-retinal fluid absorption and enhances visual rehabilitation.